Genetic engineering of crops: a ray of hope for enhanced food security - Gill, Sarvajeet Singh (Landes Bioscience, 2014)
Crop improvement has been a basic and essential chase since organized cultivation of crops began thousands of years ago. Abiotic stresses as a whole are regarded as the crucial factors restricting the plant species to reach their full genetic potential to deliver desired productivity. The changing global climatic conditions are making them worse and pointing toward food insecurity. Agriculture biotechnology or genetic engineering has allowed us to look into and understand the complex nature of abiotic stresses and measures to improve the crop productivity under adverse conditions. Various candidate genes have been identified and transformed in model plants as well as agriculturally important crop plants to develop abiotic stress-tolerant plants for crop improvement. The views presented here are an attempt toward realizing the potential of genetic engineering for improving crops to better tolerate abiotic stresses in the era of climate change, which is now essential for global food security. There is great urgency in speeding up crop improvement programs that can use modern biotechnological tools in addition to current breeding practices for providing enhanced food security.